Clinicopathologic Features of Peripheral T-Cell Lymphoma in Sub-Saharan Africa. Issue 1 (2nd February 2021) - Fitzpatrick, Megan J; Sayed, Shahin; Moloo, Zahir; Kayembe, Mukendi K A; Roberts, Drucilla J; Pham, Thu-Anh; Xi, Liqiang; Raffeld, Mark; Louissaint, Abner; Sohani, Aliyah R
Abstract: Objectives: Peripheral T-cell lymphomas (PTCLs) are heterogeneous, clinically aggressive, and rare. Subtype distribution varies by geographic location; however, data from sub-Saharan Africa (SSA) are lacking. We sought to elucidate clinicopathologic features of PTCL in SSA. Methods: We reviewed PTCL consultation cases from three SSA countries. PTCL subtype was determined per 2017 World Health Organization classification. Cases with sufficient material were evaluated by polymerase chain reaction for human T-cell leukemia virus type 1 (HTLV-1) and T-cell receptor γ ( TCRG ) rearrangement. Results: Among 32 cases, median age was 45 years and male-to-female ratio was 1.7. Thirty (94%) of 32 cases required additional workup for subclassification. PTCL, not otherwise specified (PTCL-NOS) was the most common subtype (13/32, 41%), followed by PTCL with T-follicular helper phenotype (6/32, 19%) and systemic anaplastic large cell lymphoma (6/32, 19%). Four (16%) of 25 cases were Epstein-Barr virus positive (EBV+) (2/2 extranodal natural killer/T-cell lymphoma, 1/13 PTCL-NOS, and 1/4 angioimmunoblastic T-cell lymphoma with EBV+ immunoblasts). Two (15%) of 13 patients with PTCL-NOS were human immunodeficiency virus positive. No cases with evaluable DNA (0/15) were HTLV-1 positive, and 9 of 10 showed clonal TCRG rearrangements. Conclusions: In comparison to Western studies, PTCLs from SSA show similar subtype distribution and male predominance but a younger age at diagnosis. Appropriate diagnosis of PTCL requires extensive ancillary testing not readily available in low-income countries, including much of SSA.